Authentic leadership development: scrutiny of an apparent paradox - Calheiros, António (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
Leadership has long been a topic of interest for both academics (Hiller, DeChurch, Murase, & Doty, 2011; Sanders & Davey, 2011) and practitioners (Bennis, 2007; George, 2003). Academics have tried to understand the concept and identify its consequences and determinants. Practitioners have focused their efforts in its training and development hoping to reap its promised benefits. Over the last decade, authentic leadership has emerged as the fashionable leadership theory. More than just promising impacts on performance and subordinates’ work satisfaction, authentic leadership addresses management’s long term demand for and ethic and moral commitment (Ghoshal, 2005; Rosenthal et al., 2007). Authentic leadership is “a process that draws from both positive psychological capacities and a highly developed organizational context, which results in both greater self-awareness and self-regulated positive behaviors on the part of leaders and associates, fostering positive self-development” (Luthans and Avolio, 2003). The components of authentic leadership’s self-regulated authentic positive behaviours are balanced (non-prejudice) processing, relational orientation and internalized moral perspetive. One key point of authentic leadership is the authenticity of leaders, which can be defined as “knowing, accepting, and remaining true to one’s self” (Avolio et al., 2004). Recent research (Ford & Harding, 2011) have argued that this demand for one’s true self privileges a collective (organizational) self over an individual self and thereby hampers subjectivity to both leaders and followers, and could lead to destructive dynamics within organizations. This paper discusses the seeming paradox of developing authenticity in leaders, (namely addressing the issues raised by Ford & Harding) and clarifies the aim of authentic leadership development. It also assesses the suitability of traditional leadership development methodologies in meeting the challenges posed by a process-based approach to leadership with a focus on individual and social identification.